Intangible Capital and Leverage - Horsch, Philipp; Longoni, Philip; Oesch, David (Journal of Financial and Quantitative Analysis, 2021)
Abstract We investigate the causal effect of intangible capital on leverage. To address endogeneity, we exploit patent invalidations by a U.S. court in which judges are randomly assigned to cases. Differences in judge leniency provide exogenous variation in the probability that firms’ patents are invalidated. Using this probability as an instrument for exogenous losses in intangible capital, we find a patent invalidation leads to a 14.1% reduction in leverage, suggesting that intangible capital causally supports leverage. This local average treatment effect is stronger in firms that use patents as loan collateral and in less creditworthy as well as smaller firms.